HUBUNGAN ANTARA PENGGUNAAN KONTRASEPSI DENGAN KEJADIAN FIBROADENOMA MAMMAE (FAM) DI RUMAH SAKIT BUDI KEMULIAAN BATAM - Muhammad Rifki; Rizka Audina; Malahayati Rusli Bintang (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2024)
Background: Fibroadenoma mammae (FAM) is a breast tumor that is painless, unilateral, benign (non-cancerous), in the form of a solid lump, and does not contain fluid. It mostly appears in women between the ages of 14 and 35. FAM cases increase every year, accompanied by concerns about lumps around the breasts which are often mistaken for malignancy. Although the exact cause of FAM is not known, several factors have been identified as risk factors for FAM, including contraceptive use, getting pregnant at a young age, and being on hormonal therapy. Methods: This research method is observational analysis with a case control approach. The sampling technique used was nonprobability sampling with a purposive sampling technique with a sample size of 80 respondents (40 case groups and 40 control groups). Analysis uses the chi square test. Results: The results of this study found a relationship between contraceptive use and the incidence of fibroadenoma mammae (FAM). The results of the chi square statistical test showed a p value of 0.000 (<0.05). Conclusion: Based on this research, it was concluded that there was a relationship between contraceptive use and the incidence of fibroadenoma mammae (FAM) at Budi Kemuliaan Hospital Batam at a relatively weak level of relationship strength. Keywords: Contraceptive, Woman, Fibroadenoma mammae (FAM)